Nigeria : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2003)
This Selected Issues paper and Statistical Appendix analyzes the key challenges facing Nigeria. The paper discusses issues and prospects in the oil and gas sector, provides basic information on the sector, and highlights the importance of strengthened governance. It describes the fiscal policy rules, which presents options for Nigeria based on the experience of other countries. The paper highlights that implementing a fiscal policy rule is identified as one possible way for Nigeria to stabilize public expenditures in the face of volatile oil prices.